KARAKTERISTIK PERTUMBUHAN JABON DARI PROVENAN SUMBAWA PADA TINGKAT SEMAI DAN SETELAH PENANAMAN - Tri Pamungkas Yudohartono (Jurnal Pemuliaan Tanaman Hutan, 2013)
Growth is one of important and economic traits of jabon. Growth is not only determined by environment but also genetic factor. Seedling quality and suitable site would create well growing plants. This research is purposed to know growth characteristic of jabon from Sumbawa  provenances in nursery and after plantation as well as the effect of genetic factor on growth characteristic of jabon. Research design used in nursery is Completely Randomized Design with 24 mother trees and 3  replications. Each replication comprises 10 seedlings. Totally, there are 720 seedlings. Experimental design used in progeny test plot of jabon is Randomized Complete Block Design. Breeding strategy used in this plot was subline system with single treeplot. Number of families used are 28 families. Each family comprises 20 blocks that were also functioned as replication. The results showed that there were significant differences in terms of height and diameter among the tested families at all observation ages. Family heritability estimates for height were high at at all observation ages. Family heritability estimates for diameter were high at nursery and moderate after plantation.